Multi-view 3D human pose estimation combining single-frame recovery, temporal integration and model adaptation - Hofmann, Michael; Gavrila, Dariu M (2009 IEEE Conference on Computer Vision and Pattern Recognition, 2009)
We present a system for the estimation of unconstrained 3D human upper body movement from multiple cameras. Its main novelty lies in the integration of three components: single frame pose recovery, temporal integration and model adaptation. Single frame pose recovery consists of a hypothesis generation stage, where candidate 3D poses are generated based on hierarchical shape matching in the individual camera views. In the subsequent hypothesis verification stage, candidate 3D poses are reprojected to the other camera views and ranked according to a multiview matching score. Temporal integration consists of computing best trajectories combining a motion model and observations in a Viterbi style maximum likelihood approach. Poses that lie on the best trajectories are used to generate and adapt a texture model, which in turn enriches the shape component used for pose recovery. We demonstrate that our approach outperforms the state of the art in experiments with large and challenging real world data from an outdoor setting. The new data set is made public to facilitate benchmarking.